GIAO-DFT calculation of 15 N NMR chemical shifts of Schiff bases Accuracy factors and protonation effects - Semenov, Valentin A (Magnetic resonance in chemistry : MRC, 2018)
Copyright © 2018 John Wiley & Sons, Ltd.